Measuring job satisfaction from the perspective of interpersonal relationship and faculty workload among academic staff at public universities in Kelantan, Malaysia - Noraani Mustapha; Zaizura Che Zakaria (International Business Information Management Association, 2013)
The objective of this study is to determine the influence of interpersonal relationship and daily workload on job satisfaction among lecturers in public universities in Kelantan. Sample was randomly selected through systematic procedure and data was collected from 320 academic staffs using self-administered research questionnaires. Data was analysed using descriptive analysis to describe demographic profile of respondents and Pearson Product Moment Correlation to test the relationship between variables. The result indicated that there was positive significant relationship between interpersonal relationship and job satisfaction, whereas daily workload and satisfaction was inversely correlated. Organization should consider these variables in promoting satisfaction among employees in order to enhance organizational citizenship.